1993
DOI: 10.1300/j002v19n01_05
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the Displaced Farm Family:

Abstract: With the current state of affairs in the farm economy, more and more farms are foreclosing and rural businesses are shutting down. With this loss of employment, rural families are being uprooted and being forced to relocate in other rural areas or, more typically, to urban areas. This change of lifestyle goes beyond the breadwinner to affect the entire family. This paper focuses upon the family ramifications of such moves. Attention will be turned to the specific problems of the father, the mother, and the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Social support networks at the family level can mediate the negative emotional and behavioral patterns associated with economic hardship in immigrant families and encourage parental warmth and acceptance, which then indirectly promote positive functioning in children's adaptation (Lou & Siantz, ). Jurich, Collins and Griffin () suggested that informal helping networks are of crucial importance to the adjustment of migrant families.…”
Section: Introductionmentioning
confidence: 99%
“…Social support networks at the family level can mediate the negative emotional and behavioral patterns associated with economic hardship in immigrant families and encourage parental warmth and acceptance, which then indirectly promote positive functioning in children's adaptation (Lou & Siantz, ). Jurich, Collins and Griffin () suggested that informal helping networks are of crucial importance to the adjustment of migrant families.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng and Berry (1991) revealed that Chinese sojourners in Canada reacted to their problems with less wishful thinking, self-blame and the seeking of information support. In a study on rural-urban migration of Americans, Jurich, Collins and Griffin (1993) revealed that displaced farmers used ineffective coping strategies such as an increase in alcohol consumption and physical violence to deal with problems associated with resettlement.…”
Section: The Functions Of Copingmentioning
confidence: 99%